Excitonic linewidth of organic quantum wires generated in reduced dimensionality matrices. Issue 18 (25th April 2016) - Barisien, Thierry; Legrand, Laurent; Mu, Zhao; Hameau, Sophie
Abstract : Nanostructured crystalline film achieving a 2D bath for single conjugated polymer chain linewidth spectroscopy. Abstract : Luminescent organic quantum wires are generated in diacetylene crystalline ultra-thin films grown on orientation-inducing surfaces obtained by poly-tetrafluoroethylene (teflon) deposition. The films are characterized by atomic force microscopy showing that quasi-two-dimensional surroundings are achieved. In this particular environment, pure dephasing processes still determine the wires' homogeneous emission widths, measured using micro-photoluminescence. Coherence times that are slightly shorter in the films also exhibit a distinctive temperature dependence. A model inspired by semiconductor physics for exciton–phonon coupling accounts for the observed behaviour and evidences the role of matrix dimensionality on the coherence properties.